Development of aerosolized palm-based nanoemulsion system containing quercetin for pulmonary delivery of lung cancer - Arbain, Noor Hafizah (2018)
Quercetin (QT) is an attractive natural compound, has been extensively investigated for its pharmacological effects towards lung cancer. However, clinical applications of QT as chemotherapeutic agent are limited due to low water solubility and low bioavailability. A new nanoemulsion system to enhance the solubility of QT in the dispersed phase and its bioavailability was developed for pulmonary delivery of lung cancer. Aerosolized palm-based nanoemulsion system containing QT was carried out using high energy emulsification method by dissolving QT in oil phase and then it was added into aqueous phase. Screening of oils and surfactants were done by solubility and emulsification test. From the results, it showed that the combination of palm oil esters (POE), ricinoleic acid (RC) with ratio 1:1 (wt. / wt.) and Tween 80 gave the highest solubility (0.66 mg/mL) of QT compared to other oil mixtures and showed the smallest droplet size was obtained (131.5 nm). These compositions were used for further optimization of nanoemulsion formulation. The formulation was optimized using Mixture Experimental Design (MED) and Artificial Neural Network (ANN). The composition effects of the mixture of POE:RC (1.50–4.50 wt. %), lecithin (1.50–2.50 wt. %), Tween 80 (0.50–1.00 wt. %), glycerol (1.50–3.00 wt. %), and water (88.00–94.95 wt. %) towards the droplet size and volume median diameter (VMD) as the responses were studied. The mathematical model from MED suggested three optimized formulations named OPT 1, OPT 2 and OPT 3 with specific amount of POE:RC (1.50, 3.40 and 4.50 wt. %), lecithin (1.50 and 2.50 wt. %), Tween 80 (1.50 wt. %), glycerol (1.50, 3.00, and 2.43 wt. %) and water (93.95, 89.56, and 89.02 wt. %) gave predicted response values of droplet size (110.42 nm, 132.95 nm and 146.04 nm) and VMD (5.959 μm, 4.576 μm and 4.378 μm). These values showed good correlation with the actual values of droplet size (110.30 nm, 131.40 nm and 150.60 nm) and VMD (5.882 μm, 4.557 μm and 4.266 μm). The results from ANN analysis gave no significant differences between the actual and predicted values of VMD with lower residual standard error than MED. From the physicochemical characterizations, the optimized formulations (OPT 1, OPT 2 and OPT 3) possessed suitability for pulmonary application. The droplet size measured in Transmission Electron Microscopy (TEM) was consistent with the size obtained using Zetasizer analysis and showed the droplets of nanoemulsion were spherical. These optimized formulations exhibited good stability against phase separation and remained in nano-sized under storage. Stability evaluation shows these formulations were stable under centrifugation test, freeze thaw cycle test and storage at 4 °C for three months. The evaluation of aerosol nanoemulsion showed efficient delivery with more than 90% aerosols output, higher percent dispersed and percent inhaled of drug formulation. The aerosols delivery properties for OPT 1, OPT 2 and OPT 3 yielded mass median aerodynamic diameter (4.25 ± 0.38 μm, 3.20 ± 0.07 μm and 3.09 ± 0.05 μm), fine particle fraction (70.56 ± 6.33%, 89.01 ± 1.37% and 90.52 ± 0.10%) and geometric standard deviation (1.96 ± 0.07, 1.76 ± 0.03 and 1.77 ± 0.03) that suitable for aerosolization to be inhaled in the lung. The optimized nanoemulsions demonstrated the sustained QT release of about 18.33 ± 0.32%, 24.15 ± 1.68% and 26.75 ± 2.20% within 48 hours and there were in adherence to Korsmeyer‘s Peppas mechanism. Cytotoxicity analysis showed the developed formulation has a better cytotoxicity action on human lung cancer cells (A549) compared to human lung fibroblast cells (MRC5). In conclusion, a stable palm-based nanoemulsion system containing QT was successfully developed in this study and shows potential for pulmonary delivery of lung cancer.